Steric control of the in/out sense of bridgehead substituents in macrobicyclic compounds: isolation of new "crossed chain" variants of in/out isomers. Issue 89 (8th September 2015) - Stollenz, Michael; Taher, Deeb; Bhuvanesh, Nattamai; Reibenspies, Joseph H.; Baranová, Zuzana; Gladysz, John A.
Abstract : When an in, out isomer of a macrobicyclic dibridgehead diphosphine is combined with two equiv. of a gold(i ) Lewis acid of sufficient bulk, the resulting adduct is obtained as a topologically novel out, out isomer with "crossed chains". Abstract : Isomers of the cage like dibridgehead diphosphine P((CH2 )14 )3 P (1 ) are treated with Ph3 PAu(2, 6-C6 H3 (Trip)2 ) (2 equiv.; Trip = 2, 4, 6-C6 H2 (iPr)3 ). With out, out -1, workup gives out, out -1·(Au(2, 6-C6 H3 (Trip)2 ))2 (46%), as confirmed by a crystal structure. With in, out -1, crystallization affords not in, out -1·(Au(2, 6-C6 H3 (Trip)2 ))2, but rather an out, out isomer in which one of the (CH2 )14 segments threads through the macrocycle formed by the other two. Implications for mechanisms of interconversion of in, out isomers are analyzed.